Виховна діяльність монахинь Чину Святого Василія Великого - Дмитришина, Надія (Видавництво Національного університету "Львівська політехніка", 2009)
A short investigation of the educational system of Basilian monks was made in this article. It was analyzed the main forms and methods of their work in specialized schools and gymnasiums which were organized at Basilian monasteries.
Keywords: Basilian monks; moral and national education; gymnasium; teachers’ seminary; educational circles